When Monuments Get Alive - Contemporary Social/Art Practices in Croatia - Potkonjak, Sanja; Pletenac, Tomislav (2010)
Remembrance is seen as the product of a community of people which resembles and evokes the most precious values of collective identity and communicates contingent needs of the present. In contrast to collective-memory-practices, this paper aims to explore individual practices of remembering performed by three Croatian artists. The paper explores performative projects of Marijan Crtalić – Project Target – where the socialist sculptural heritage gets to be reinterpreted by military teleologies ; than Siniša Labrović, whose project restages partisan pieta vulnerability, and Igor Grubić and his project of redressing socialist sculptures. The projects point to the interconnectedness of past and present, memory and politics, collective versus individual via art. Acting as individuals, those artists have tangled the questions of how societies tend to renegotiate the meaning of art coming from the socialist past alongside the renegotiation of memory. Re-evoking socialism in their work, those three artists stand for individual interpellation of collective amnesia pointing to the process of remembrance as highly contextual practice placed in-between individual responsibility, political activism and humanism in general. By trying to re-animate or make sculptures re-personalize human figures, those art projects are meant to criticize, comment and envision the existing usage of cultural memory as well as to offer post-utopian insights on socialist and transitional utopia.
Projekt MZOS
ENG